Transcriptome-based variations effectively untangling the intraspecific relationships and selection signals in Xinyang Maojian tea population - Cheng, Lin (2023)
As one of the world’s top three popular non-alcoholic beverages, tea is economically and culturally valuable. Xinyang Maojian, this elegant green tea, is one of the top ten famous tea in China and has gained prominence for thousands of years. However, the cultivation history of Xinyang Maojian tea population and selection signals of differentiation from the other major variety Camellia sinensis var. assamica (CSA) remain unclear. We newly generated 94 Camellia sinensis (C. sinensis) transcriptomes including 59 samples in the Xinyang area and 35 samples collected from 13 other major tea planting provinces in China. Comparing the very low resolution of phylogeny inferred from 1785 low-copy nuclear genes with 94 C. sinensis samples, we successfully resolved the phylogeny of C. sinensis samples by 99,115 high-quality SNPs from the coding region. The sources of tea planted in the Xinyang area were extensive and complex. Specifically, Shihe District and Gushi County were the two earliest tea planting areas in Xinyang, reflecting a long history of tea planting. Furthermore, we identified numerous selection sweeps during the differentiation of CSA and CSS and these positive selection genes are involved in many aspects such as regulation of secondary metabolites synthesis, amino acid metabolism, photosynthesis, etc. Numerous specific selective sweeps of modern cultivars were annotated with functions in various different aspects, indicating the CSS and CSA populations possibly underwent independent specific domestication processes. Our study indicated that transcriptome-based SNP-calling is an efficient and cost-effective method in untangling intraspecific phylogenetic relationships. This study provides a significant understanding of the cultivation history of the famous Chinese tea Xinyang Maojian and unravels the genetic basis of physiological and ecological differences between the two major tea subspecies.